2019
DOI: 10.3390/w11050946
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Urban Stormwater Runoff on Cyanobacteria Dynamics in A Tropical Urban Lake

Abstract: Worldwide, eutrophication and cyanobacteria blooms in lakes and reservoirs are a great concern for water resources management. Coupling a catchment hydrological model and a lake model has been a strategy to assess the impact of land use, agricultural practices and climate change on water quality. However, research has mainly focused on large lakes, while urban reservoirs and their catchments, especially in tropical regions, are still poorly studied despite the wide range of ecosystem services they provide. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 72 publications
0
5
0
1
Order By: Relevance
“…Yan et al, (2019) indicated that stormwater runoff was regarded as the largest source of total nitrogen (TN), chemical oxygen demand (COD), and ammonium nitrogen (NH4 + -N) in the Taihu Basin, China. Silva et al, (2019) demonstrated that increasing impervious areas in the catchment enhanced the nutrient inputs from stormwater runoff, carrying total suspended solids (TSS), total phosphorus, and nitrate (NO3 -) into Lake Pampulha, Brazil at the beginning of the wet season.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al, (2019) indicated that stormwater runoff was regarded as the largest source of total nitrogen (TN), chemical oxygen demand (COD), and ammonium nitrogen (NH4 + -N) in the Taihu Basin, China. Silva et al, (2019) demonstrated that increasing impervious areas in the catchment enhanced the nutrient inputs from stormwater runoff, carrying total suspended solids (TSS), total phosphorus, and nitrate (NO3 -) into Lake Pampulha, Brazil at the beginning of the wet season.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Upadhyay et al (2021) indicated that variations in soil temperature and moisture conditions under climate change scenarios may hinder future soil carbon dynamics by mediating soil nutrient availability in urban soils in Varanasi city, India. Understanding the effects of climate change on urban tropical areas is also crucial for addressing issues like eutrophication and pollution (Silva et al, 2019) and for flood damage estimation and mitigation (Tabucanon et al, 2021). Therefore, when planning for sustainable, biodiverse, and resource-efficient tropical cities, it is essential to consider these social and economic impacts.…”
Section: Climate Changementioning
confidence: 99%
“…These challenges encompass a wide range of areas, including human health, productivity, urban planning, sanitation, resilience, and biodiversity. They are already manifesting as increased risks of heat stroke and disease transmission (e.g., Burkart et al, 2011;Coccolo et al, 2016;Lee J. M. et al, 2019), reduced human comfort due to high levels of thermal stress (e.g., Roth, 2007;Méndez-Lázaro et al, 2016;Ramsay et al, 2021), heightened energy consumption driven by increased cooling demand (e.g., Gamero-Salinas et al, 2021), decreased water availability and heightened pollution (e.g., Chow and Yusop, 2013;Pérez-Villalona et al, 2015;Silva et al, 2019), alterations in local flora and fauna distribution caused by inadvertent climate modification (e.g., Roth and Chow, 2012;Oh et al, 2018;Alue et al, 2022), air pollution challenges (e.g., Vailshery et al, 2013;Nipen et al, 2022), and the resilience challenges of the health-sanitation nexus (Macedo et al, 2022). Therefore, the development of tools and mechanisms to adapt to climate change and conserve urban resources and biodiversity in tropical cities is crucial due to the challenges they face.…”
Section: Introductionmentioning
confidence: 99%
“…Destacam-se ainda as temáticas vinculadas às doenças de veiculação hídrica (Aguiar et al, 2019); aos aspectos relacionados à prevenção de doenças e propostas de promoção da saúde (Souza & Freitas, 2008); a contextualização do saneamento rural (Resende et al, 2018); a execução orçamentária vinculada ao plano diretor da cidade de Teresina, no estado do Piauí (Nascimento & Gomes, 2018); e uma simulação do cenário associado ao aumento da impermeabilização na bacia hidrográfica e das cargas de sólidos suspensos totais, fósforo total e nitrato na Lagoa da Pampulha, Belo Horizonte/MG (Silva et al, 2019).…”
Section: Scienceunclassified